Equity in Access to Public Housing: A Comparative Study of Housing Policies in Jakarta and Singapore from an International Law Perspective - Farisa, Pawit Fadila Rika; Sadiawati, Diani (Dinasti Research, 2025)
The rapid urbanization in Southeast Asia has posed significant challenges in providing adequate and affordable housing, particularly for vulnerable urban groups. This article analyzes a comparative study of public housing policies in Jakarta and Singapore from the perspective of international law on the right to adequate and inclusive housing. Using a normative comparative method with a qualitative-descriptive approach, this study examines the effectiveness of each country’s housing policy based on Article 25 of the Universal Declaration of Human Rights (UDHR), Article 11 of the International Covenant on Economic, Social, and Cultural Rights (ICESCR), and General Comment No. 4 of the Committee on Economic, Social and Cultural Rights (CESCR). The findings reveal that Singapore, through its Housing and Development Board (HDB), successfully implements an inclusive public housing system with comprehensive subsidies and without discrimination based on marital status or employment type. Conversely, public housing policies in Jakarta remain exclusive due to strict administrative requirements that limit access for single individuals and informal workers. This article recommends reforming Jakarta’s public housing policies by relaxing discriminatory requirements and establishing a national public housing authority to ensure fair, inclusive, and internationally compliant housing access for all citizens.